Las memorias de Mario Onaindia: geminación e iluminaciones - Miguel Olmos (Cahiers de Civilisation Espagnole Contemporaine)
Mario Onaindia's memoirs bear witness to the efforts deployed in the construction of a personal trajectory that is also a remarkable public career within a context marked by serious historical, social and political tensions, both in the Basque Country and in Spain. The author's active search is guided by a disbelieving or skeptical attitude, whose questions may appear dramatized through duplicated textual structures. Some of these show a reflective, specular nature, in which the subject becomes an enigmatical object of his own attention. These revealing doublings allow, on the one hand, to establish milestones in time and articulate the course of remembrance; on the other, they test the coherence of the autobiographer, confronted with his inexhaustible depth of experience, either lived or remembered. Finally, they provide samples of his knowledge of contemporary political language​, and the essential keys of his ideological evolution.